+0  
 
0
125
1
avatar

Given that g is the inverse function of f, and f(3)=4, and f'(3)=5, then g'(4) = 

 

  • -1/5
  • 3/5
  • 1/5
  • 1/4
Guest May 24, 2017
Sort: 

1+0 Answers

 #1
avatar+77131 
+1

 

The derivative of the inverse function is given by :

 

g'(x)  =   1 / [ f ' (g (x) ) ]

 

Note that  ( 3, 4)  is on  " f " so   (4, 3)  is on   " g "    so.....g (4)  = 3

 

So

 

g ' ( 4)  =  1 / [ f ' ( g (4) ) ]  =   1 / [ f ' (3) ]  =   1 / [ 5 ]   =   1 / 5 

 

 

 

cool cool cool

CPhill  May 24, 2017
edited by CPhill  May 24, 2017

20 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details